2
$\begingroup$

I need to show the steps to prove this identity: $$\sin^4{x} = \frac{3-4\cos{2x}+\cos{4x}}{8}$$

I know that $\cos{2x}=\cos^2{x}-\sin^2{x}$. From there I do not know what to do. The solution should look like:

$$\sin^4{x}=sin^4{x}$$

I need to prove the right side equals the left side.

$\endgroup$
  • $\begingroup$ You could use deMoivre's theorem. $\endgroup$ – user122283 Mar 2 '14 at 19:18
  • 1
    $\begingroup$ I don't think the OP knows about techniques in complex analysis. $\endgroup$ – Mr.Fry Mar 2 '14 at 19:20
  • $\begingroup$ And $\cos 4x= \cos^2 2x - \sin^2 2x$ and you will get there if you are persistent. $\endgroup$ – Mark Bennet Mar 2 '14 at 19:37
  • $\begingroup$ mathworld.wolfram.com/Double-AngleFormulas.html $\endgroup$ – lab bhattacharjee Mar 3 '14 at 4:46
4
$\begingroup$

If you know $\sin x = \frac{e^{ix}-e^{-ix}}{2i}$ and $\cos x = \frac{e^{ix}+e^{-ix}}{2}$, then just expand using the binomial theorem: $$\sin^4 x = \frac{e^{4ix} - 4e^{3ix}e^{-ix}+6e^{2ix}e^{-2ix}-4e^{ix}e^{-3ix}+e^{-4ix}}{(2i)^4}$$ $$=\frac{e^{4ix}+e^{-4ix} -4e^{2ix}-4e^{-2ix} + 6}{16}$$ $$=\frac{\frac{e^{4ix}+e^{-4ix}}{2} -4\frac{e^{2ix}+e^{-2ix}}{2} + 3}{8}$$ $$=\boxed{\frac{\cos 4x -4\cos 2x + 3}{8}}$$ as desired.

$\endgroup$
  • $\begingroup$ Don't care if I'm not allowed to say thanks. This saved my butt in my numerical solutions to PDE's class. $\endgroup$ – rocksNwaves Feb 12 '18 at 2:25
  • $\begingroup$ (blush) Message understood. Complex analysis gives such cool shortcuts. Glad it helped.Pass it on, @rocksNwaves! $\endgroup$ – MPW Feb 12 '18 at 3:36
1
$\begingroup$

Hint: $$\cos{2x}=\cos^2{x}-\sin^2{x}=1-2\sin^2{x}\\ \implies \sin^2{x}=\frac{1-\cos{2x}}{2}$$

$\endgroup$
1
$\begingroup$

Hint: $(\cos^2 x-\cos2x)(\cos^2 x-\cos 2x)=(\sin^2 x)^2$

$\endgroup$
0
$\begingroup$

You could also use the fact that $\text{Re} ((\cos x + i \sin x)^4) = \text{Re} (\cos 4x + i \sin 4x)$.

$\endgroup$
0
$\begingroup$

Let $ z = \cos(\theta) +i \sin(\theta)$

We can then find through De Moive's formula and the fact that $\cos -\theta = \cos \theta$ and $\sin -\theta = - \sin \theta$:

$ z - \frac1z \equiv 2i\sin\theta$

Thus: ($i^4=1$)

$ (z-\frac1z)^4 \equiv 16\sin^4\theta$

Expanding the RHS:

$ (z-\frac1z)^4 \equiv z^4 - 4z^2 + 6 - 4z^{-2} + z^{-4}$

Then subsituting $z$ back into the equation. (The $\sin$s will cancel out)

$ (z-\frac1z)^4 \equiv 2\cos4\theta - 8\cos2\theta + 6$

Finally dividing by 16 to get $\sin^4\theta$:

$\sin^4\theta = \frac {\cos4\theta - 4\cos2\theta + 3} 8$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.